Arctic Security Strategies and the North Atlantic States - Wegge, Njord (Arctic Review on Law and Politics, 2020)
New uncertainties in international relations have presented several states in the West with important choices regarding their national strategies for the Arctic. This article analyzes security challenges in the Arctic and North Atlantic region, as understood by some key North-Atlantic states, namely: the USA, Canada, Denmark, Norway, the UK, Germany and France. By analyzing how, or to what degree, the colder east-west security landscape since 2014 is reflected in these selected North Atlantic states’ Arctic security strategies, this article seeks to improve our understanding of how the security situation in the northernmost part of the world is developing and being understood. Through applying a traditional understanding of security, the article identifies similarities but also significant differences among the Arctic and North-Atlantic states. Most notable when comparing the strategies is the rather unique global perspective laid out in the US security strategy for the region. The British, Norwegian, Danish and Canadian perspectives, on the other hand, stand out as more regional in nature. Germany displays a rather low profile in its approach to international security in the Arctic, considering its economic status in Europe. France reveals a strong concern for Arctic shipping and freedom of navigation, a perspective similar to the USA’s, but with less global ambition.